Distribution and foraging by the leaf-cutting ant, Atta cephalotes L., in coffee plantations with different types of management and landscape contexts, and alternatives to insecticides for its control - Varón Devia, Edgar H. (2006)
Tesis (Ph. D.) College of Graduate Studies University of Idaho (EEUU) / CATIE, Turrialba (Costa Rica), 2006